A Double Issue of The Pomegranate The First Decades of Contemporary Pagan Studies - Clifton, Chas 1951- (2016)
Tracing the history of Pagan studies, primarily in the United States, I look back to the Pomegranate's inspiration, Iron Mountain: A Journal of Magical Religion and touch on some high points in the history of Pagan studies book publication well.
Keywords: Pagan Studies; Paganism; Wicca; Witchcraft